Lipidomic Profile Revealed the Association of Plasma Lysophosphatidylcholines with Adolescent Obesity. (13th December 2019) - Wang, Yang; Jiang, Chang-Tao; Song, Jie-Yun; Song, Qi-Ying; Ma, Jun; Wang, Hai-Jun
Abstract : Objective . The human lipidomic profile reflects lipid metabolism, including the early phase of pathophysiological changes associated with diseases. An investigation of the association between the plasma lipidomic profile and adolescent obesity might provide new insights into the biological mechanisms of obesity. Therefore, we aimed to investigate the association of the plasma lipidome with obesity in Chinese adolescents using lipidomics. Methods . Using a combination of liquid chromatography and electrospray ionization tandem mass spectrometry, we quantified 328 lipid species from 24 lipid classes and subclasses in 100 male adolescents aged 14–16 years who were categorized into four groups: (1) normal weight with traditional normal clinical plasma lipid levels (NN); (2) normal weight with traditional abnormal clinical plasma lipid levels (NA); (3) obese with traditional normal clinical plasma lipid levels (ON); and (4) obese with traditional abnormal clinical plasma lipid levels (OA). The concentrations of all the lipid species were compared between obese and normal-weight adolescents at different traditional clinical plasma lipid levels using the Kruskal–Wallis test followed by the Mann–Whitney U test. A partial least squares discriminant analysis (PLS-DA) was applied to select lipids with a significant ability to discriminate adolescent obesity. Results . The lipidomic profile distinguished obese adolescents from normal-weight subjects. Regardless of whether traditional clinical plasma lipid levels were normal or abnormal, we observed a significant reduction in the levels of five lysophosphatidylcholines (LPC) species (LPC18:2, LPC18:1, LPC20:2, LPC20:1, and LPC20:0) in the obese group compared with the normal-weight group (difference = −31.29% to −13.19%; P = 9.91 × 10 − 5  to  2 . 28 × 10 − 2 ). The ability of these five LPC species to discriminate adolescent obesity was confirmed in the PLS-DA model. Conclusions . The findings provided evidence for the association of some LPC species with adolescent obesity. The discriminatory effects of five LPC species were identified between normal-weight and obese adolescents, independent of traditional clinical plasma lipid levels. These results will provide a basis for validation in subsequent studies.